Intuitionistic Fuzzy Semi δ-Preopen Sets and Intuitionistic Fuzzy Semi δ-Precontinuity - Samajh Singh Thakur; Chandra Prakash Rathor; Jyoti Pandey Bajpai (Journal of the Indonesian Mathematical Society, 2021)
The purpose of this paper is to introduce the concepts of fuzzy semi δ-preopen sets and fuzzy semi δ-precontinuous mappings in intuitionistic fuzzy topological spaces and obtain some of their properties and characterizations.